Glutamate at the phosphorylation site of response regulator CtrA provides essential activities without increasing DNA binding - Siam, Rania (Oxford University Press, 2003)
The essential response regulator CtrA controls the Caulobacter crescentus cell cycle and phosphorylated CtrA∼P preferentially binds target DNA in vitro. The CtrA aspartate to glutamate (D51E) mutation mimics phosphorylated CtrA∼P in vivo and rescues non-viable C.crescentus cells. However, we observe that the CtrA D51E and the unphosphorylated CtrA wild-type proteins have identical DNA affinities and produce identical DNase I protection footprints inside the C.crescentus replication origin. There fore, D51E promotes essential CtrA activities separate from increased DNA binding. Accordingly, we argue that CtrA protein recruitment to target DNA is not sufficient to regulate cell cycle progression.